Малярські інкорпорації в поезії західноукраїнських художників міжвоєння - Мочернюк, Наталія; Mochernyuk, Nataliya (Східноєвропейський національний університет імені Лесі Українки, 2013)
У статті розглянуто різні види мистецьких інкорпорацій у поетичних текстах Святослава Гординського, Володимира Гаврилюка та Івана Крушельницького. Мистецькі цитати є одним із аспектів інтермедіальних стратегій авторів. Біографічні нотатки, ефразиси, професійна малярська лексика складають комплекс мистецьких включень у поезію.The various types of art incorporations in the poetic texts of Sviatoslav Hordynsky, Volodymyr Havrylyuk and Ivan Krushelnytsky are examined. The art quotations are one of the aspects of author’s intermedial strategies. Intermedial typology which based on the interpretation of relations in semiotic triangle foresees three interart types (projection, transposition, transfiguration). Accordingly, interart incorporations form the transfiguration base. Biographic notes, ekphrasis, professional painting vocabulary made the complex of art intervention in the poetry. The dominant art inclusions in the works of each author are accented. The main attention to paid to the ekphrasis in the poetry works of Sviatoslav Hordynsky. The professional art terms in Volodymyr Havrylyuk’s poetic texts are distinguished. The zero ekphrases in the context of the poem ‘The gladness of life” by Ivan Krushelnytsky are observed.
The painting incorporations in the poetry of Western Ukrainian artists between the war
Keywords: поезія; образотворче мистецтво; живопис; екфразис; інтертекст; poetry; fine art; painting; ekphrasis; intertext